Analisis Perbedaan Abnormal Return Sebelum dan Sesudah Pengumuman Ex-Dividend Date pada Perusahaan Manufaktur di Bursa Efek Indonesia Periode Tahun 2011-2016 - Ahmad Setiawan Nuraya; Yuliani Larasati (STIE Indonesia Banking School, 2018)
The aim of the research is to analyze the distinctions of investor reactions based on its abnormal return before and after dividend disclosure at the ex-dividend date. An event study is applied in the period of 10 days before and after. Research is directed on the manufacturing sector that disclosed its dividend on Bursa Efek Indonesia (BEI) – Indonesia Stock Exchange in the period of the Year 2011-2016. Purposive sampling is used on a total of 15 companies with its 112 events (of dividend disclosures). The main finding concludes that there is no significant difference in the abnormal return before and after dividend disclosure.